A formação do artista/docente: um estudo autoetnográfico - Gouveia, Francisco de Assis (2024)
The aim of this research was to compare pedagogical practices applied to the training of actors in the construction of theatrical performances and the pedagogical practices, developed for the teaching of theater in the basic education system, analyzing their contributions to the training of the artist/teacher. The idea-concept of artist/teacher was the central theoretical category, articulated with Fischer's (2002) understanding of the Total Being, Ostrower's (2003) Conscious-Sensitive-Cultural Being, Icle's (2010) Shaman and Silva's (2010) Student/Actor. This is an autoethnographic study, in which the researcher analyzed his experiences as an actor and as a drama teacher, in the logbooks and other records that constituted the materiality of this research. Based on the content of the diaries and other records, the focus was to reflect on the pedagogical and artistic approaches identified in both the theater teaching experiences and the artistic training practices, in dialogue with the theoretical approaches and practices of the artist-teacher today. The objective is also to demystify these two exercises as isolated forms, since by being an artist/teacher, the researcher broadens their "ear" and "voice" in understanding the field of theater, which contributes to understanding their exercises and raises awareness of a full artist/teacher, creator, subject of their act and trainer of themselves.